2022
DOI: 10.1097/jw9.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle habits and impact of the Mediterranean diet on facial acne severity in French women: a case-control study

Abstract: Acne is a common benign inflammatory disease, but it has a significant psychosocial impact. The role of the diet in the development of acne is controversial. Some daily foods such as milk and fast-release sugars tend to promote acne. The Mediterranean Diet (MD) is based on virgin olive oil and nuts that are rich in polyphenols with anti-inflammatory properties. The aim of this study was to assess an association between the adherence to the MD and the severity of facial acne in French women. A case-control obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…For instance, adherence to the Mediterranean diet, specifically the use of extra virgin olive oil as the primary fat in the diet, reduced the disease severity among patients with suppurative hidradenitis by reducing the Hurley stage and the severity score [ 71 ]. Moreover, adherence to the Mediterranean diet seems to be negatively associated with the severity of acne; thus, increasing the consumption of foods specific to the Mediterranean diet can benefit people with acne [ 70 , 72 ].…”
Section: Gut Microbiome-targeted Therapies For Psoriasismentioning
confidence: 99%
“…For instance, adherence to the Mediterranean diet, specifically the use of extra virgin olive oil as the primary fat in the diet, reduced the disease severity among patients with suppurative hidradenitis by reducing the Hurley stage and the severity score [ 71 ]. Moreover, adherence to the Mediterranean diet seems to be negatively associated with the severity of acne; thus, increasing the consumption of foods specific to the Mediterranean diet can benefit people with acne [ 70 , 72 ].…”
Section: Gut Microbiome-targeted Therapies For Psoriasismentioning
confidence: 99%
“…The study revealed that adherence to the MD is not associated with acne diagnosis or severity. In contrast, three previous studies adopting a case‒control design have suggested that high adherence to the MD may be protective against acne [ 39 41 ]. This contrast may be attributed to variations in research settings and methodologies, thereby limiting comparisons to the present study.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the content and arrangement of the questionnaire were found to be culturally appropriate for the population targeted in this study. Furthermore, previous studies exploring the association between adherence to the MD and acne use the same tool for assessment, which might facilitate comparison to these studies [ 40 , 41 ]. The MEDAS questionnaire comprised 12 inquiries regarding the frequency of food consumption and two queries related to dietary habits.…”
Section: Methodsmentioning
confidence: 99%
“…A cross‐sectional observational study found low adherence to MD in acne patients compared to individuals with healthy skin 55 . Another study showed a negative correlation between following MD and acne severity 56 . Recent research has shown promising results with probiotic administration in individuals with acne 36,57 …”
Section: Resultsmentioning
confidence: 99%
“…55 Another study showed a negative correlation between following MD and acne severity. 56 Recent research has shown promising results with probiotic administration in individuals with acne. 36,57…”
Section: Air Pollution and Smokingmentioning
confidence: 99%